Vitamin D and Autism Spectrum Disorder: An Intriguing Association - Raqshan Wajih Siddiqui; Tabish Wajih Siddiqui; Shiza Wajih Siddiqui (Annals of Child Neurology, 2024)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that affects the overall cognitive, emotional, social, and physical health of the affected individual. It is characterised by challenges in social communication and interaction, repetitive and stereotyped behaviours, and narrow interests. The pathogenesis of ASD is thought to involve a combination of genetic and environmental factors. Increasing evidence suggests that vitamin D deficiency during pregnancy and early childhood may contribute to the development of ASD. While studies have indicated that vitamin D supplementation can significantly improve symptoms of ASD, the underlying mechanism remains elusive. This review summarises the association between vitamin D levels and ASD, explores potential mechanisms underlying vitamin D's role in ASD, and examines the effect of vitamin D supplementation on ASD symptoms.